PEMBUATAN PETA SITUASI SKALA 1: 500 LOKASI 1 DUSUN KALICANGAK DAN SEKITARNYA, DESA BELUK, KECAMATAN BAYAT, KABUPATEN KLATEN, PROPINSI JAWA TENGAH - , FENDY PRASETYA TRIATMAJA; , Ir. Christine Noegroho K ,Su.Pj ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job Training Activity (PKL) is an annual eventof geomatics courses that has to be followed by every student as the final evaluation, the basics knowledge usedin the Job Training Activity have been given duringthe lecture. Work performed in planimetris are mapping situation.Mapping the situationis a form of mapping which includes planimetric and contour measurement. Initial measurements of the mapping work is the making of the basicpoints of the mapping framework (TKDP) were fairly evenly in the area to be mapped using a total station theodolite measuring instrument and a carpenter's level. This TKDP will be abond of details that are the object of the elements that exist on the surface of the earth which will be illustrated in the map. The depiction of the map manuscript is described using Surpac software that is then used for testing the map, while themap depiction of the situation carried out using ArcGIS software. The end result of the activities of the Job TrainingActivity is a situation map scale of 1: 500 and printed on A1 size paper and can present spatial information in the region.